2012
DOI: 10.1186/1476-9255-9-38
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of TNFR1 (CD120a) and TNFR2 (CD120b) on subpopulations of human monocytes

Abstract: BackgroundThree subpopulations of monocytes can be distinguished in human blood: classical (CD14++CD16−), intermediate (CD14++CD16+), and nonclassical (CD14+CD16++). CD16 expressing monocytes are expanded in patients with sarcoidosis and in various other inflammatory diseases. In sarcoidosis, it is unclear whether either intermediate, nonclassical or both CD16 expressing monocytes are responsible for this increase. Data relating to the monocyte subpopulations is receiving increasing attention, but the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 20 publications
4
30
0
1
Order By: Relevance
“…24, 26-28 Although there has been conflicting data that demonstrate a pathogenic role for TNFR2 in DSS-induced colitis, 29 inflammatory monocytes are more likely to express TNFR1, while TNFR2 upregulation in colonic epithelial cells is observed in patients with inflammatory bowel disease. 30, 31 Altogether, these studies are consistent with our data since Nlrp6 −/− mice that receive rTNFα early during DSS treatment exhibit reduced intestinal inflammation and bacterial translocation.…”
Section: Discussionsupporting
confidence: 90%
“…24, 26-28 Although there has been conflicting data that demonstrate a pathogenic role for TNFR2 in DSS-induced colitis, 29 inflammatory monocytes are more likely to express TNFR1, while TNFR2 upregulation in colonic epithelial cells is observed in patients with inflammatory bowel disease. 30, 31 Altogether, these studies are consistent with our data since Nlrp6 −/− mice that receive rTNFα early during DSS treatment exhibit reduced intestinal inflammation and bacterial translocation.…”
Section: Discussionsupporting
confidence: 90%
“…A possibility is that CD16 was lost due to cellular activation via TLRs, as previously shown (29). We therefore defined the IL-12-producing subpopulation as HLA-DR + , CD38 lo , and CD120b + , which is consistent with the phenotype of inflammatory monocytes (29,30). Notably, the production of IL-12 by CD16 +…”
Section: Discussionmentioning
confidence: 53%
“…We also demonstrated that in patients with sarcoidosis the intermediate CD16 + CD14 ++ blood monocyte population was expanded. Since this monocyte subset has been shown to express the highest levels of the TNF receptor TNFR131, monocytes in sarcoidosis may be more responsive to TNF.…”
Section: Discussionmentioning
confidence: 99%